Appendices to the statement of claim: between demanding and exces-sive condency - L. A. Terekhova; I. V. Merenkov (Правоприменение, 2023)
Subject of the research. The article deals with the problems of access to court and violation of the adversarial principle in case of unreasonable decision by the court to leave the claim without movement. The purpose of the research: to determine the nature of possible violations of the principles of access to justice and competitiveness at the time of filing a claim and to identify a way to eliminate violations. Research methods: formal-legal method, anal-ysis, synthesis, formal-logical method.The main results. The procedural and legal consequences of noncompliance with the requirements for a statement of claim is the issuance by the court of a decision to leave the statement without movement, in which it indicates the grounds for this procedural action and the period during which the plaintiff must eliminate the circumstances that served as the basis for leaving the statement of claim statements without movement (part 1 of article 136 of the Civil Рrocedure Code of the Russian Federation). The problem is that an appeal against this ruling is not provided. In cases where the shortcoming of the submitted application is the absence of evidence in the annex to it, which is impossible for the applicant to obtain, the applicant will not be able to comply with the court order or appeal against the ruling issued by the court. In fact, the applicant is deprived of access to the court. In this situation, the plaintiff cannot count on any court assistance in obtaining (reclaiming) the necessary evidence: the court provides assistance in collecting evidence only at the stage of preparing the case for trial, i.e. after the case has been opened. The Constitutional Court of the Russian Federation did not see any problems in this situation, because it is impossible to independently appeal the ruling of a court of general jurisdiction on leaving the statement of claim without movement, however, failure to comply with the requirements specified in it is the basis for issuing a ruling on the return of the statement of claim, against which a private complaint can be filed. The paradoxical nature of such a statement that leaving the statement of claim without movement does not prevent the further movement of the case. In our opinion, the problem under discussion would be solved much easier if Article 136 of the Civil Рrocedure Code of the Russian Federation had provided for the obligation of the court to accept the statement of claim, that is, to initiate a civil case after the deadline set by the court for the presentation of evidence, provided that the applicant justifies the impossibility of obtaining requested documents for reasons beyond his control. Then it would be possible for him to receive the assistance provided by law from the side of the court. Otherwise, the person may lose access to the court. Conclusions. The court has the right to point out the shortcomings of the statement of claim, which is carried out by issuing a ruling on leaving the statement of claim without movement, indicating the deadlines for execution. If the plaintiff fails to submit the requested evidence within the time limit set by the court, the court returns the claim to the plaintiff. In this moment the balance in the implementation of the principles of competitiveness and judicial activity is violated. Therefore, it is proposed in this situation to accept the statement of claim after the expiration of the period appointed by the court for the provision of evidence, and to assist the plaintiff in obtaining it.